Indicadores de sucesso em projeto: desenvolvimento de um sistema para seleção de critérios e fatores de sucesso condicionado ao contexto do projeto - Sposito, Lincoln (2024)
Considering the substantial annual investments in projects, which represent a significant portion of organizational activities and global financial movement, precise project evaluation becomes paramount. Consequently, project success emerges as a critical factor in organizational success, as project failures pose risks to reputation, financial losses, and poor business performance. In this regard, numerous studies have been conducted to assess project success; however, few have evaluated the project context. This thesis posits that project success constitutes a second-order formative construct. This construct is composed of the conceptual dimensions: success in project management and success of the project itself. Both dimensions are fundamental for a holistic understanding of project success. This thesis demonstrates that context is a pivotal research axis, influencing the selection of critical success factors and project success criteria. Therefore, this thesis aims to develop a management system for project success indicators based on critical factors and success criteria conditioned by the project context. To achieve this goal, three studies were conducted. Study 1 aimed to identify success criteria and critical factors related to different project contexts. As a primary outcome, this study classifies the identified success criteria and factors by context and project type, thus contributing to a better understanding of specific and generic critical success factors for each context to enhance project success. Study 2 sought to propose a management tool for selecting critical factors and success criteria that would influence project success. Drawing on inputs from Study 1, this study’s main outcome was the categorization of scale items by project context, critical success factors, success criteria, and project success dimension. This study’s contribution was the proposition of a model that allows managers and researchers to identify project success evaluation items. Study 3 aimed to validate the use of the project success indicators management system. Similarly, based on inputs from previous studies, this study’s main outcome was the validation of a systemic process that enables the structuring of project data, products, and stakeholder perceptions, potentially allowing for more precise measurement at different times and by different individuals throughout the project lifecycle. The studies facilitated the classification of success criteria and factors identified by project context, enabling the categorization of the items from the 104 scales assessed in Studies 1 and 2 within the proposed hierarchy of context, critical factors, criteria, and project success dimension. Thus, the principal outcome of this thesis was the proposition and validation of a systemic process that allows for the structuring of project data, products, and stakeholder perceptions, enabling a more precise evaluation of success conditioned by the context. The theoretical and practical contributions, respectively, impact the advancement of the project context discussion and its relationship with critical factors, success criteria, and success evaluation indicators, and the development and validation of a project success indicators management system registered as a computer program at the National Institute of Industrial Property. This research aligns with Research Line 2: “Project Management,” associated with the Graduate Program in Project Management – PPGP UNINOVE. This thesis is also in line with other research by its advisor linked to the core projects “People Management and Project Management”.